Христианство в Удмуртии: история и современность / Ю. М. Ивонин - Ивонин Юрий Михайлович (Удмуртия, 1987)
Экземпляры: (20190205) / Инвентарный номер: 18146 / Цена: 0.15 / Сис.шифр: 86.37(2Рос.Удм) / Авт.знак: И 25 / ГРНТИ: 21 / ББК: 86.37(2Рос.Удм)